2013
DOI: 10.1111/jphp.12032
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of different flavonoids against myocardial ischaemia/reperfusion injury in Langendorff-perfused rat hearts

Abstract: Some flavonoids exhibit direct cardioprotective effects against the injury induced by drastic I/R and this pharmacological property seems to be related to their structural characteristics. Such an influence of structural requirements seems to indicate that the cardioprotective effects may be due to the interaction with specific pharmacological targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…It has been reported that CH exerts benecial effects on the cardiovascular function, with antioxidant and anti-inammation activity. Previous work has proved that CH could reduce ischemia-reperfusion injury in a Langendorff-perfused rat heart model (Testai et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CH exerts benecial effects on the cardiovascular function, with antioxidant and anti-inammation activity. Previous work has proved that CH could reduce ischemia-reperfusion injury in a Langendorff-perfused rat heart model (Testai et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…ISO is also identified to create oxidative stress or amplify oxidative hassle by means of configuration of adrenochromes through its auto-oxidation, which is concerned in the production of extremely toxic oxygen-derived free radicals and augments generation of thiobarbituric acid reactive substance as increase in lipid peroxidation [62,63]. In the present study, we observed that AP protected the myocardium from ISO-induced myocardial membranous injury via positively enhanced hemodynamic, electrocardiographic, biochemical and histopathological parameters, suggesting that its cardioprotective action has been reported to improve cardiac function and improve the action of PPARc receptor signalling [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…This channel is structurally similar to that expressed on the sarcolemma and is involved in vasodilatation that, at the mitochondrial level, plays a crucial role in I/R events. Indeed, naringenin promoted reduced mitochondrial calcium uptake and mild mitochondrial depolarization as well as restricting the probability of mitochondrial permeability transition pore (MPTP) formation and apoptotic death of myocardiocytes [66,67,68]. …”
Section: Putative Mechanisms Of Action Responsible For the Cardiovmentioning
confidence: 99%